(untitled) (Journal of Hama University, 2024)
240 milk samples from a group of dairy cows was infected with clinical mastitis, aged between three and seven years, from different herds owned by breeders in some towns and villages in the southern Hama countryside, were tested to detect the spread of Staphylococcus aureus mastitis in cows. The study has shown that the percentage of clinical mastitis prevalence among dairy cows in those areas has reached 9.23%, and the prevalence percentage of clinical mastitis caused by Staphylococcus aureus in the milk samples tested from cows was 93(38.75%), . A study of the some important risk factors associated with mastitis caused by Staphylococcus aureus, such as season, productive age, and affected quarter, showed that the highest prevalence of mastitis caused by Staphylococcus aureus was for the age group between 3-4 years, where it reached 40%, and the highest prevalence of mastitis caused by Staphylococcus was recorded. highest prevalence in the summer, reaching 40.63%, and the highest prevalence was in the hind quarters, where it reached 40%.